Exploring waste separation using an extended theory of planned behavior: a comparison between adults and children - Pan, Ji; Liu, Pingping (Frontiers in Psychology, 2024)
This study applied an extended model of the theory of planed behavior (TPB) to compare the differences in waste separation behavior between children (ages 9 to 12, N = 339) and adults (ages 18 to 66, N = 379). We examined the relations among waste separation attitude, subjective norm, perceived behavioral control, knowledge, awareness, intention, and behavior. The results showed waste separation knowledge of children was less than that of adults. Structure equation model results also revealed robust differences between children and adults. For adults, TPB variables (attitude, subjective norm, and perceived behavioral control) and knowledge are significantly positively related to their waste separation intention. Meanwhile, perceived behavioral control and intention are positively related to adults' behavior. However, for children, only perceived behavioral control and awareness are positively related to intention, and perceived behavioral control is positively related to behavior. Moreover, the predictive power of the extended TPB model on children's waste separation intention and behavior are lower than those of adults. The different results may be due to children's immature cognitive abilities. This study enhanced the understanding of the different waste separation behavior determinants between children and adults. The findings are useful for developing tailored policies and promoting children's waste separation behavior.